Evaluating the Relationship Between Performance on a Multiple-Choice Examination and Common ABA-Based Procedures. (June 2023) - Leaf, Justin B.; Cihon, Joseph H.; Ferguson, Julia L.; Milne, Christine; Leaf, Ronald; McEachin, John
To ensure the quality of training, skills developed and maintained, and expected standards for behavior analysts, several systems have been put into place across the years. Of these systems, perhaps the most widespread was the development of the Behavior Analyst Certification Board in 1998. Once all requirements are met, the final determinative step in obtaining certification is a multiple-choice examination. The use of a multiple-choice examination as the final determinative step in obtaining behavior analytic certification may create some concerns for behavior analysts. Identification of a positive correlation between the multiple-choice examination and performance may help ameliorate these concerns. The purpose of this study was to evaluate any potential correlations between scores on a popular commercially available prep examination and basic applied behavior analysis (ABA)–based autism intervention procedures with 25 professionals. Overall, the results indicated that multiple-choice examination scores were not significantly correlated with any assessments of performance.